Evaluation and Planning Control of the Ecosystem Fragmentation Due to Urban Development - Maurizio Biondi; Giovanna Corridore; Bernardino Romano; Giulio Tamburini; Pierantonio Tetè (European Regional Science Association (ERSA), 2003)
Different kinds of urban sprawl on the territory cause the ecosystems fragmentation phenomena which the planning tools often are not able to control. It's possible to measure these phenomena through some indicators that consider functional characteristics, shapes and dimensions of the urban objects (road networks and urbanised areas). On the base of these parameters we can obtain the models of different urban fragmentation scenarios, where each model is related to a range of indicator values (fragmentation landscapes). If we consider a set of target animal species linked to local ecosystems we could individuate the changing, in terms of crossing possibilities, that each species has with respect to each fragmentation urban model. When we get the possible relations among the values of fragmentation indicators and the other classic parameters that the planners use to regulate density and distribution of the future urbanised areas on the territory, we?ll can realise the credible scenarios about the environmental fragmentation conditions following the plan tool management. The new framework which the plan draws for the territory will be more or less suitable for the movement of the species that lives around and, analysing this suitability through biopermeability evaluation, will be possible to adjust the impacts of the urban transformation on the ecosystems and natural landscapes. The data and the methods used during the research program that we inserted in the present paper are relative to study area of the Italian Central Apennines, a mountain place where we can find natural areas and complex eco-mosaics, with species of fauna of international importance, and numerous small and middle urban areas ?plunged? in the ecological networks. Corresponding author: Bernardino Romano
Keywords: 330